Whole-Body SAR simulations on a prolate spheroid using different plane wave polarizations up to 100 GHz - Hernández-Bonilla, José Enrique (Instituto Tecnológico de Costa Rica, 2018)
A study on specific absorption rate (SAR) measurements using computational tools is presented. Using various numerical tools, ranging from full-wave simulators to physical optics, a prolate spheroid is irradiated by different polarized plane waves in the frequency range of 10 MHz - 100 GHz. For the low frequency range full-wave simulators were used to obtain the whole-body SAR of the prolate spheroid. When technical limitations were reached by this methodology, a physical optics approach was used to reach whole-body SAR measurements to a 100 GHz. As a side study, the electrical properties of water were studied with the goal of using them in both approaches. This project is a joint effort between the Technical University of Hamburg (TUHH) and the Technical Institute of Technology of Costa Rica (TEC).
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2018.
Keywords: Propiedades eléctricas de los materiales; Óptica; Física; SAR; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics